Cystic endosalpingiosis of the uterus-a rare entity in disguise - Shweta Choudhary; Priyanka Agnihotri; Sangita Sehgal; Arpita Jindal; Ajay Yadav (International Journal of Medical Research and Review, 2016)
Cystic endosalpingiosis is a non - neoplastic lesion characterised by multiple cysts lined with benign tubal type epithelium. Our case presented as cystic ovarian neoplasm clinically and radiologically. Patient underwent Total abdominal hysterectomy and bilateral salpingo-oophorectomy. Microscopically, the cyst consists of multiple cysts lined by benign tubal type epithelium. A diagnosis of subserosal cystic endosalphingiosis was made. Increasing awareness of this entity would be helpful in making correct diagnosis by pathologists.